Differential expression of sex hormone receptors in abdominal aortic aneurysms. (February 2017) - Villard, Christina; Eriksson, Per; Kronqvist, Malin; Lengquist, Mariette; Jorns, Carl; Hartman, Johan; Roy, Joy; Hultgren, Rebecka
Highlights: The expression of sex hormone receptors in abdominal aortic aneurysms differs from that in healthy aorta. There are greater mRNA- and protein expressions of androgen receptors in abdominal aortic aneurysms. There are lower mRNA- and protein expressions of estrogen receptor β in abdominal aortic aneurysms. Expressions of sex hormone receptors are similar in men and women with abdominal aortic aneurysm. Sex hormone activity may be associated with the development of aneurysms. Abstract: Objective: Male sex is a significant risk factor for abdominal aortic aneurysm (AAA). Female sex hormones have been reported to prevent aneurysm formation in animal models. The study aims to describe the expression profile of sex hormone receptors in the aneurysm wall of men and women with AAA and compare with unaffected controls. Methods: Aneurysm wall biopsies were obtained during elective open repair of AAA in men and women (n = 16 + 16). Aortic vessel wall from controls were obtained at organ donation (n = 6). Western blot-, mRNA expression- and immunohistochemical analyses were performed to assess the expression profile of the sex hormone receptors – androgen receptor (AR), progesterone receptor (PR), estrogen receptor α (ERα) and β (ERβ). Results: The mRNA- and protein expression levels of AR were higher in AAA compared with control aorta (7.26 vs. 5.14, P = 0.001). mRNA- and protein expression levels of ERβ were lower in AAA compared with control aorta (9.15 vs. 12.29, P < 0.001). mRNA expression levels of PR were higher in AAA compared with control aorta (8.73 vs. 6.21, P = 0.003), but could not be confirmed on protein level. The expression profile of sex hormone receptors in men and women with AAA was similar. Conclusion: Expression of sex hormone receptors differs in the aneurysmal aorta compared with unaffected aorta in men and women. A higher expression of AR and a lower expression of ERβ suggest that sex hormone activity could be associated with aneurysm development.